Exploring the potential effect of phospholipase A2 antibody to extend beef shelf-life in a beef liposome model system - Chun, Colin Kili’ohu Yukio (Kansas State University, 2022)
Phospholipase-A₂ (PLA2) is a ubiquitous enzyme that cleaves a fatty acid tail at the sn-2 position from a phospholipid (PL) in cell membranes. The resulting free fatty acids (FFA) are typically polyunsaturated fatty acids (PUFA) which are prone to lipid oxidation when exposed to pro-oxidants such as light and oxygen. Therefore, the objective of this study was to elucidate the interaction of PLA2 and a PLA2 antibody (aPLA2) on PL hydrolysis utilizing a beef liposome model system and to understand how the altered PL composition in the presence of myoglobin may affect lipid oxidation and antioxidant capacity in a retail display setting. The PL was extracted from 10 United States Department of Agriculture choice beef loins at 3d post-mortem, and PL from each steak was further split into six different treatments: 1) PL (10 mg/ml of PL); 2) aPLA10 (PL+10 µg/ml of aPLA2); 3) aPLA20 (PL+20 µg/ml of aPLA2); 4) PLA2 (PL+4 µg/ml of PLA2); 5) PLA2+aPLA10 (PL+PLA2+10 µg/ml of aPLA2); 6) PLA2+aPLA20 (PL+PLA2+20 µg/ml of aPLA2). After execution of the liposome system, an aliquot was immediately taken for PL profile analysis, FFA analysis and product ion analysis by mass spectrometry. Eighty µM of bovine myoglobin was added to the remaining samples and exposed to retail display conditions (2±2°C; 2300 lx) for 7d. At 0, 1, 4, and 7d, aliquots were taken for hydrophilic and lipophilic oxygen radical absorbance capacity (ORAC) and lipid oxidation analysis (TBARS). As expected, the PL composition was significantly altered by the PLA2 treatments, and the generation of FFAs was evident. The PLA2 treatments had significantly less relative % of total phosphatidylcholine (PC), ether-linked PC (ePC), and phosphatidylethanolamine (PE) than treatments without PLA2 (P < 0.05). Individual PL species, notably PC 36:2, 36:3, 36.4, ePC 32:4, 36:3, 36:4, PE 36:2 and 38:4 also showed greater relative % in PLA2 treatments as compared to treatments with PLA2. Product Ion analysis revealed that the major FAs involved in these altered PL were 16:0, 18:0, 18:1, 18:2 and 20:4. The FFA profile showed that treatments containing PLA2, regardless of the addition of aPLA2, had greater amounts of 16:1, 18:1, 18:2, 20:4, and 20:5 (P < 0.01), but no treatment difference were found for any of the saturated FFA such as 18:0 and 16:0 (P > 0.05). The PLA2 treatments also showed greater relative % of total lysophosphatidylcholine (LPC) and LPC 16:0, 16:1, 18:0, and 18:1 than treatments without PLA2 (P < 0.01). There was no apparent inhibition effect from aPLA2 as there was no difference between PLA2 and aPLA+PLA2 treatments in formation of FFA and in the relative % of total PL classes (P > 0.05). In addition, the altered PL composition also influenced ORAC and TBARS values. There were treatment x retail display effects for hydrophilic and lipophilic ORAC (P < 0.01), as well as in TBARS (P < 0.01). For hydrophilic ORAC, samples with PLA2 had higher antioxidant capacity than samples without PLA2 (P < 0.01). For lipophilic ORAC, samples with PLA2 also showed higher antioxidant capacity than treatments with no PLA2 at 0 d (P < 0.01), but the enhanced antioxidant capacity from the PLA2 samples faded after just 1d of retail display. For TBARS, PLA2 treatments had higher lipid oxidation than treatments without PLA2 added throughout the entire retail display period (P < 0.01). Interestingly, not only did 7d aPLA10 and aPLA20 have less lipid oxidation than PL only and all PLA2 treatments, but 7d aPLA10 and aPLA20 also had less oxidation compared to those from 4 d PLA2 (P < 0.01). This study confirmed that the hydrolysis of PL can generate extensive amount of FFAs and potentially influence lipid oxidation in meat during the retail display period. Although no inhibition effect was observed for PLA2 by the addition of aPLA2, aPLA2 by itself seemed to influence lipid oxidation with PLA2 exhibited antioxidant capacity. Further research is needed to better understand the mechanisms of aPLA2 to PLA2 interaction to elucidate the potential benefits of aPLA2 in a meat system.
Keywords: Phospholipase A2; Anti-phospholipase A2; Phospholipid; Antioxidant capacity; Lipid oxidation; Lipidomics